A review of Deuterixys Mason from China, with description of three new species (Hymenoptera, Braconidae, Microgastrinae) - Zheng, Minlin; Song, Dongbao (Zootaxa, 2020)
The genus Deuterixys Mason, 1981 (Hymenoptera, Braconidae, Microgastrinae) is revised for China, with three new species described: D. jilinensis Zheng & Song, sp. nov., D. longitarsus Zheng & Song, sp. nov. and D. shennongensis Zheng & Song, sp. nov. A key to the Old World species of Deuterixys is presented.